Operation and energy evaluation of diesel and hybrid trains with smart switching controls. (November 2021) - Din, Tajud; Tian, Zhongbei; Li, Kang; Hillmansen, Stuart; Roberts, Clive
Abstract: Energy and environmental sustainability in urban rail transport have attracted substantial attention in the last decade. In the UK, about 29% of the current train fleets are run solely on diesel fuel, and the UK Government has pledged to remove all diesel-only trains by 2040. One option to achieve this ambitious goal is replacing diesel trains with hybrid trains. However, little has been done to evaluate the operational performance of replacing diesel trains with hybrid trains on the same track. This paper develops a novel Hybrid Train Simulator which can analyse the driving performance and energy flow among multiple energy sources (diesel, hydrogen and battery). Several practical case studies are presented based on typical mainline railways in the UK. Operation performance using diesel trains and hybrid trains is compared. This paper also proposes automatic smart switching control between multiple power sources according to the altitude of the route for hybrid trains. The case studies indicate that hybrid trains increase the journey time due to their low power capacity but improve energy efficiency significantly. Besides, implementing auto-switching on hybrid trains can reduce energy consumption by 6% compared with benchmark hybrid trains.